Tracking the tiny target - Queen, Connie (Love inspired suspense., 2023)
"When a three-year-old boy is kidnapped, deputy sheriff Chandler Murphy and his search-and-rescue K-9 partner are on the case. And when the child's mother, Bristol Delaney, insists on helping, he can't turn her away. But someone is dead set on stopping the investigation. Can Chandler guarantee Bristo's safety and rescue the missing child before the trail goes cold?"--Back cover.